Penerapan Model Predator-Prey pada Proses Perkecambahan Biji Kacang Hijau - Regitha Lorenza (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
Mungbean (Vigna radiata L.) is a type of legume plant with high protein and a short life of approximately 2 months. This plant is found in all regions of Indonesia. The morphology of the mungbean plant consists of roots, stems, leaves, flowers, fruits, and seeds. Mungbean seeds have nutritional content but are in an inactive (dormant) form, after being germinated, the nutrient content is activated, thereby increasing digestibility for humans. A germination is a biological event that occurs from a seed in a dormant state until it becomes a growing seed. Sprouts derived from green bean seeds are called bean sprouts. The germination process can increase the nutritional value of mungbeans, thus, in this journal, a study was conducted to determine the growth model of mungbean sprouts in order to determine the best time to consume bean sprouts. In modeling the growth of green bean sprouts, a predator and prey model is used, which is resolved numerically using the fourth order Runge-Kutta method. From the research conducted, it can be concluded that the maximum nutrition of bean sprouts is on the third day since germination begins.